“Os brancos estão chegando, trazendo escola, missão e saúde”: relações yanomami através da escola - Jabra, Daniel (2022)
Having as a starting point Adriano Pukimapɨwëteri Yanomami's narrative about the arrival of non-indigenous and their schools, this dissertation proposes to reflect on the relationships historically built through the school between the Yanomami groups of the Marauiá River region (AM) and their non-indigenous partners, and also of how they have appropriated it to update and maintain their networks of inter-community relations of alliance and enmity. The Yanomami groups in Marauiá have had different experiences of schooling: the Salesian and the one called in Brazil as differentiated, and the adoption and defense of these two systems has become a stage for the expression of political differences and alliance between the groups, also operating in the processes of producing difference and territorial occupation. The arrival of the school serves for the forces of colonization and sedentarization, but also for the indigenous strategies of counter-effectuation of colonization, so that the adoption of schools by Yanomami groups occurs in parallel with a continuous process of elaboration of what the school is and what they have sought with her and through her. In this context, the political actions of certain Yanomami groups, including Adriano's, began to use the schools to counteract, or at least reduce, the violence of contact and assimilation.